Homeopathy for back and neck pain - Stone, Ursula (Kensington Books, 1999)
Learn ways to treat the pain of muscle strains and pulls, stress-related disorders, premenstrual discomfort, over-exertion, accidents, and other back injuries with homeopathic medicine.